Student learning styles'influence on manual skill proficiency and academic performance of dental proper students - Quiec, Charlyn L.
In a study conducted by Davies et al in 1997, there showed a significant difference on how the various learning styles of Kolb affect academic performance and interviewing skills of medical students. This study attempted to see whether student learning styles have an influence on the academic as well as manual performance or dental proper students in the University of the Philippines College of Dentistry. The study used the Kolb's Learning Style Inventory among 130 students from the second, third and fourth year dental proper students enrolled in SY 1999-2000. The result showed that 42.3% are Assimilators, 26.15% are Divergers, 16.15% are Accommodators and 15.38% are Convergers. Assimilators (x=2.74) seemed to especially excel in FPD Lecture while Convergers (x=2.13; x=2.88) seemed to excel in Oral Anatomy and Restorative Dentistry 12 Laboratory. In all laboratory courses, Divergers had the lowest grade or mean scores. Findings show that Assimilators tend to excel in their academic performance while Convergers tend to excel in manual performance. The result also showed that Divergers tend to do poorly in manual performance.